2001
DOI: 10.1063/1.1420576
|View full text |Cite
|
Sign up to set email alerts
|

Patterning organic–inorganic thin-film transistors using microcontact printed templates

Abstract: We report the simple, low-cost, and parallel fabrication of patterned organic–inorganic thin-film transistors (TFTs) by microcontact printing a molecular template on the substrate surface prior to film deposition. We printed molecules with hydrophobic tail groups on the gate oxide surfaces of TFTs to chemically, differentiate the substrate surface and confine the self-assembly of thin films, deposited from solutions flooded across the entire surface, to the transistor channels. TFTs are fabricated with good de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
86
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 22 publications
2
86
0
Order By: Relevance
“…For example, microcontact printing may provide sufficient resolution and registry for large-area circuits. High/low energy surface patterns have been used to define the placement of perovskite semiconductor islands deposited from a flooding methanol solution [43]. Predefined surface energy contrast has also been employed to define the widths of lines of conducting polymers delivered via inkjet printing of aqueous solutions [11,91].…”
Section: Low-cost Patterning Methodologiesmentioning
confidence: 99%
“…For example, microcontact printing may provide sufficient resolution and registry for large-area circuits. High/low energy surface patterns have been used to define the placement of perovskite semiconductor islands deposited from a flooding methanol solution [43]. Predefined surface energy contrast has also been employed to define the widths of lines of conducting polymers delivered via inkjet printing of aqueous solutions [11,91].…”
Section: Low-cost Patterning Methodologiesmentioning
confidence: 99%
“…In the past few years, a variety of materials, such as inorganic single crystals, [76] organic-inorganic hybrid materials, [77] conjugated polymers, [28,78,79] and oligomers, [28,80] have been successfully patterned via solution-processing using self-assembled monolayers (SAMs) as templates. Recently, it has been demonstrated that SAMs can also function as templates for patterning organic semiconductor single crystals, by serving as selective nucleation sites [81] or (de)wetting patterns.…”
Section: Solution-processing Techniquesmentioning
confidence: 99%
“…[ 110 , 111 ] In a wetting-controlled, parallel, lowtemperature process, although only demonstrated on Si wafer, μ CP was used to pattern a "molecular template" on the substrate directing thin fi lms by spincoating into the desired pattern to fabricate TFTs. [ 112 ] Contact printed, organic active matrix backplanes on 5 × 5-inch PET sheets, with 10 μ m wide and 20 μ m spaced source and drain electrodes forming bottom-contact transistors, have been demonstrated as well ( Figure 5 ). [ 113 ] …”
Section: Microcontact Printing ( μ Cp)mentioning
confidence: 99%